Open-source architecture and questions of intellectual property, tacit knowledge, and liability. Issue 3 (2nd April 2020) - Dortheimer, Jonathan; Margalit, Talia
Abstract : Inspired by open-source and crowd sourcing technologies, the concept of 'open-source architecture' has been increasingly used to describe collaborative architectural design (CoDesign) in recent years. In this article, we aim to show that major related issues remain unresolved. As such, they limit the wider adaptation of open-source methods to the world of architecture. We focus on the following issues: first, architectural theorists have not addressed the meaningful limitations and possibilities of these methods in architecture, including the ramifications of sharing knowledge with end users; second, professional architects already share ideas through existing networks that resemble open-source models; third, projects that have aspired to democratise design processes in the recent past have encountered difficulties in sharing tacit professional knowledge with non-professional users; finally, existing open-source licences exclude professional liability which is the bedrock of relations between the architect, their clients, and regulatory authorities in architecture. To arrive at open-source architecture, we argue that these issues need to be further investigated and resolved. The article concludes with reflections on the exchange of knowledge and ideas between professionals and non-professionals, architects and users, and how this can be simplified by using crowd-sourcing technologies.